Formation of independent skills physical training for university students - Tretyakov A.A. ,; Shcherbin D.V. ,; Posokhova T.V. ,; Tsagolova N.G. , (Theory and Practice of Physical Culture, 2024)
Objective of the study was to develop pedagogical recommendations for developing students’ skills in organizing independent physical training. Methods and structure of the study. The pedagogical experiment was carried out on the basis of Belgorod and Moscow universities. 340 senior students took part in it. In the experimental group, complexes of special and methodological classes were used, as well as various activities aimed at mastering the skills of independent physical training during the semester at least once a week. To assess the level of mastery of the skills to organize independent physical training, a survey was conducted. Results and conclusions. Of all the skills assessed, gnostic skills received the highest score. This emphasizes that knowledge, which must be up-to-date, plays an important role in organizing independent physical training. Organizational skills are considered important. As part of the classes, it is necessary to solve problems related to the formation of self-educational competence of students. This will allow, upon graduation, not to experience difficulties in organizing and conducting independent physical training to maintain a high level of physical fitness.